Life cycle of phytoreoviruses visualized by electron microscopy and tomography - Miyazaki, Naoyuki; Nakagawa, Atsushi; Iwasaki, Kenji (Frontiers in Microbiology, 2013)
Rice dwarf virus (RDV) and Rice gall dwarf virus (RGDV), members of the genus Phytoreovirus in the family Reoviridae, are known as agents of rice disease, because their spread results in substantial economic damage in many Asian countries. These viruses are transmitted via insect vectors, and they multiply both in the plants and in the insect vectors. Structural information about the viruses and their interactions with cellular components in the life cycle are essential for understanding viral infection and replication mechanisms. The life cycle of the viruses involves various cellular events such as cell entry, synthesis of viral genome and proteins, assembly of viral components, viral egress from infected cells, and intra- and inter-cellular transports. This review focuses on the major events underlying the life cycle of phytoreoviruses, which has been visualized by various EM imaging techniques, including cryo-electron microscopy and tomography, and demonstrates the advantage of the advanced EM imaging techniques to investigate the viral infection and replication mechanisms.